The process of developing the professional identity of the Nurse Case Care Manager: A Grounded Theory Study - Bertuol, Maria; Tagliabue, Cristina; Ventre, Valentina; Cusenza, Piero; Taffurelli, Chiara; Sarli, Leopoldo; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2020)
Background and purpose. The Nurse Case Care Manager (NCCM) is still an emerging figure in the Italian healthcare context. The knowledge of the dynamics inherent in the process of identity development shows how they can be decisive for the affirmation and recognition of this new role. The aim of the study was therefore to analyse the psychosocial processes of developing the identity of the NCCM for a better understanding of the variables that influence its development. Methods. A qualitative study with Grounded Theory method was conducted. From December 2018 to January 2019, 20 semi-structured interviews were given to the NCCM of the Emilia Romagna Region and the Lombardy Region. The analysis of the material has led to a structuring of the theoretical model on the processes of development of professional identity. Results. Two main conditions have been identified: that of the “LOST CASE MANAGER” and that of the “CASE MANAGER DIRECTOR”. This process requires time, perseverance, courage and personal skills. Two transversal background concepts have been identified, namely “available space” and “relationship with the family”. Conclusion. The process of developing the NCCM’s professional identity encounters several obstacles. Among these, in particular a lack of recognition by operators highlighting the need for greater organizational clarity in the context in which the professional operates, in order to facilitate the inclusion of the NCCM clarifying skills and effectiveness profile.